MINIMUM WAGE AS ONE OF THE MAIN STATE SOCIAL GUARANTEES - Kivalov, Serhii; Tarasenko, Viktoriia; Voloshyna, Svitlana; Chanyshev, Rashyd; Shchukin, Oleksandr (Revista Gênero e Interdisciplinaridade, 2020)
The definition, goals of the minimum wage, the criteria for its determination, the sphere of application of the system of setting the minimum wage, the procedure for its establishment, as well as regulation and implementation were analyzed in the article. Comparative legal analysis was carried out of the acts of national labor legislation for compliance with international and European standards, enshrined in conventions and recommendations of the International Labor Organization , Attention is drawn to the fact that Ukraine has not yet undertaken obligations under paragraph 1 of Art. 4 of the European Social Charter (revised).The essence and significance of the minimum wage as one of the main state social guarantees is revealed, taking into account changes and amendments, made by the Legislation of Ukraine. The ratio of the category "minimum wage" and the category "subsistence level set for able-bodied persons on January 1 of the calendar year" is determined.